ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT SISWA DALAM PENGAMBILAN KEPUTUSAN MEMILIH JURUSAN AKUNTANSI KELAS X DI SMK N 1 DEMAK - Hayurika, Turina Lasriza; Arief, Sandy (Fakultas Ekonomi, Universitas Negeri Semarang, 2015)
The purposes of this research are: (1) to determine the factors that affecting interest students in decision-making choose of accounting class X in SMK N 1 Demak, (2) to determine which factor that has the greatest or most dominant to interest students in decision-making choose of accounting class X in SMK N 1 Demak. To be able to determine the factors that affect interest decision-making choose of accounting, then a research was conductedÂ using factor analysis and descriptive analysis methods.The population of this study were all students class X of accounting amounting to 114 students. The samples were 53 members chosen using proportional random sampling technique. The variables of this study were the talent, potential self, intelegent, family, school, peers group, employments opportunities, lack of participation, lack of representation, treatment not fair, dimensions access, dimensions of learning process, dimensions mastery, dimensions control, and dimensions of benefits. The data collection method used was questionnaires, then analyzed by factor analysis with SPSS 16.0 for windows.Based on the results of the factor analysis, from the 15 items there is 1 variables that should be dropped, while the remaining 14 variables formed 3 new factor, namely the internal factor students, the external factor students, and gender difference. Third new factors have a totl value of the coefficients variant 58,19%. The dominant factor influential namely gender difference which embeds in it values the coefficients variant 27,157%.Â Dimensions control with load factor of 0.674, lack of partisipation with load factor 0.671, dimensions of benefits with load factor of 0.740, dimensions of learning process with load factor of 0.612, dimensions mastery with a load factor of 0.610, with a load factor of lack of representation 0,823, and the unjust treatment with a charge with load factor of 0.597.